Antibiotics resistance of Vibrio spp. isolated from diseased seabass and tilapia in cage culture - Hamdan, Ruhil Hayati; Peng, T. L.; Ong, Bee Lee; M. Y. S., Suhana; Hamid, N. H.; Mohamad, Nora Faten Afifah; Manaf, Sharifah Raina (Indonesian Center for Animal Research and Development, 2016)
Vibriosis has become one of the most important bacterial diseases in marine cultured organisms in recent years. This study was focusing on isolation and identification of Vibrio spp. isolated from diseased seabass (Lates calcarifer), tilapia (Oreochromis niloticus) and seawater from Sri Tujuh lagoon in East Coast of Malaysia; also determination of antibiotic resistance patterns among Vibrio spp. Vibrio species isolated from diseased seabass in Pantai Sri Tujuh, Tumpat, Kelantan were screened for their antibiotic sensitivity patterns by Kirby-Bauer method. A total of 47 isolates belonging to three different species were identified which are V. parahaemolyticus, V. vulnificus, and V. alginolyticus. In this study, high incidence of erythromycin, chloramphenicol and sulfamethoxazole resistance was observed among the Vibrio isolates, whereas all isolates were susceptible to oxytetracycline. Vibrio isolates were 96% resistant to one or more different classes of antibiotic, and 17 different resistance patterns were identified. The MAR index of 0.4 indicating the Vibrio spp. in these farmed fish might have been indiscriminately and continuously exposed to those antibiotics during culturing stages of the fish. This study showed that multidrug-resistant Vibrio spp. were common in diseased seabass and tilapia cultured at Sri Tujuh lagoon. These essential findings suggested involvement of seafood in transmission of these pathogen to human. In addition, oxytetracycline can be used as a treatment to combat vibriosis in diseased seabass and tilapia.